Whistler Waves in the Plasmasphere Boundary Layer: Nonlinear Parametric Excitation. Issue 13 (1st July 2019) - Mishin, Evgeny; Sotnikov, Vladimir; Gershenzon, Naum; Sharma, Amit
Abstract: We present the initial results of numerical simulations of nonlinear coupling between quasi‐electrostatic lower hybrid oblique resonance and fast magnetosonic waves, which was suggested to explain the observations of Very Low Frequency (VLF) electromagnetic emissions at frequencies well above the lower hybrid resonance frequency in the turbulent plasmasphere boundary layer. These emissions represent a distinctive subset of the substorm/storm‐related VLF whistler activity contributing to the alteration of the outer radiation belt boundary. As the turbulent plasmasphere boundary layer is interior to the plasma sheet inner boundary and thus devoid of substorm‐injected kiloelectron volt electrons, the "standard" whistler generation mechanism must be excluded. The simulations show that the parametric coupling of lower hybrid oblique resonance and magnetosonic waves creates VLF electromagnetic emissions with the spectral characteristics consistent with the observations. Key Points: The results of numerical simulations of parametric interaction of lower hybrid oblique resonance and fast magnetosonic waves are presented VLF whistler waves at frequencies well above the lower hybrid resonance are excited due to beating of the two electrostatic pump waves The simulation results are consistent with the in situ observations in the turbulent plasmasphere boundary layer